The doll test : choosing equality - Weatherford, Carole Boston, 1956- (Carolrhoda Books, 2024)
"Narrated by dolls, this book tells the little-known story of two Black psychologists, Kenneth and Mamie Clark, who used Black and white dolls in their research about the effects of school segregation on children"--